Edupreneurship to Improve Financial Literacy Through Market Day Activities in Children Aged 5–6 Years - Riska Amalia; Nahdiyah Hidayah (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to improve the financial literacy of children aged 5–6 years through edupreneurship-based market day activities. Financial literacy is important to be introduced from an early age so that children are able to understand the concept of money and simple transactions. The study employed a Classroom Action Research (CAR) method based on the Kemmis and McTaggart model, conducted in two cycles. The research subjects consisted of 20 children in Group B at TK ABA Somawangi, Banjarnegara Regency. Data were collected through observation and documentation based on financial literacy indicators, including recognition of types of money, understanding of money value, and the ability to conduct buying and selling transactions. The results showed an improvement in children's financial literacy from 40% in the pre-cycle to 60% in Cycle I and significantly increased to 83% in Cycle II. Improvements occurred across all indicators and met the success criteria of ≥ 80%. Based on these findings, it can be concluded that edupreneurship-based market day activities are proven effective in improving the financial literacy of children aged 5–6 years.